CORRELATION BETWEEN CHRONIC TRAMADOL ADMINISTRATION AND DISTURBANCES ACTIVITY OVARIAN FOLLICLES AND ENDOMETRIUM IN FEMALE RATS - Mohamed, Mostafa Abd El-Mounem; Elsaied, Mahmoud Hemy; Abo Baraka, Waleed Ezat; Mandour, Esam Mohamed Ragab (Journal of medical and pharmaceutical sciences, 2018)
Researchers on toxic effects of tramadol on female reproductive system are limited and need to be extended for more confirmations and results So the purpose of this study was to detect the possible correlation between chronic tramadol administration and disturbances activity of ovarian follicles and endometrium in female rats. The study was involved twenty-five adult female rats divided into 4 experimental groups(A, B, C&D); received tramadol by different doses and methods and control group (CON) received normal saline. Histopathological examination was done for ovaries and uterus to all groups. The result in group A showing mild and moderate decreased number of growing follicles and ovulated oocytes with cystic changes and hyper cellular stroma with recovery in 80% in group C. In group B showing moderate and severe decreased of ovulation with recovery in 40% of growing follicles in group C. Also in group A showing moderate atrophied endometrial gland with obvious recovery in the group C. While in group B showing severe atrophy of endometrial gland with recovery in 60 % in group D. In conclusion; positive correlation between chronic tramadol administration and disturbances activity of ovarian and growing follicles in female rats. which is not permanent as it can be reversed after withdrawal of the tramadol. It is recommended that; clinical studies are needed to approve present results about the effect of tramadol on male and female genital system.